Gestión administrativa y su incidencia en la toma de decisiones del Centro Médico de Especialidades Liramed del cantón Montalvo provincia de Los Ríos en el periodo 2023. - Montes Soto, Luis Alejandro (2025)
To achieve proper administrative management, it is essential to have processes of planning, organization, and resource control, which influence competitiveness and sustainable development. The methods and techniques show shortcomings at the LIRAMED Medical Specialty Center, located in the canton of Montalvo, in the province of Los Ríos. For this reason, this research aims to evaluate the impact of administrative management on decision-making. The research and analysis process was conducted under a mixed approach (quantitative-qualitative) with an exploratory and descriptive design. The study used surveys for patients and interviews with managers to identify administrative management deficiencies and their impact on service delivery, along with empirical analysis methods. The results show inefficiencies in service delivery, prolonged waiting times, poor coordination in resource allocation, and missed opportunities. Additionally, the absence of a quality system, a lack of strategic planning, and the absence of a structured decision-making system are factors that affect the center's profitability and sustainability. Based on these findings, improvement proposals are established, including the implementation of technology to digitize administrative processes, optimize the management of medical appointments, and improve communication with patients. It is also proposed to strengthen administrative staff training, establish performance measurement mechanisms, and apply management-by-objectives models to enhance efficiency and decision-making.